INTRAVITREAL SULFUR HEXAFLUORIDE INJECTION FOR THE TREATMENT OF VITREOMACULAR TRACTION SYNDROME. Issue 4 (April 2016) - Day, Shelley; Martinez, Jose A.; Nixon, Peter A.; Levitan, Mark; Dooner, James W.; Wong, Robert W.; Harper, Clio A.
Abstract : Purpose: Vitreomacular traction (VMT) syndrome can cause symptomatic metamorphopsia and decreased visual acuity. Although it is typically treated with vitrectomy or intravitreal ocriplasmin injection, these procedures can be invasive and costly. The purpose of this retrospective, consecutive case series was to evaluate the efficacy of intravitreal expansile sulfur hexafluoride gas injection for the treatment of symptomatic VMT syndrome. Methods: Nine eyes of 9 patients with symptomatic VMT syndrome on spectral domain optical coherence tomography received an intravitreal injection of 0.3 mL of 100% sulfur hexafluoride. The primary outcome was the number of eyes with release of VMT on spectral domain optical coherence tomography at 1 month after treatment. Secondary outcomes included change in visual acuity and central subfield thickness 1 month after treatment. Results: Five patients (55.6%) had release of VMT on spectral domain optical coherence tomography by 1 month after injection. Two patients who had Stage I macular holes before injection had closure of the macular holes. Mean visual acuity at 1 month improved slightly after injection by 0.09 logMAR units, although this change was not statistically significant ( P = 0.15). Central subfield thickness on spectral domain optical coherence tomography decreased by an average of 35.3 microns after injection ( P = 0.004). All eyes with release of VMT had pretreatment vitreomacular adhesion of less than 521 microns and none had epiretinal membranes. One patient (11.1%) developed a peripheral retinal hole at 1 month after injection. Conclusion: Intravitreal injection of expansile sulfur hexafluoride gas is a low-cost and minimally invasive alternative for the treatment of symptomatic VMT syndrome. Further study is warranted. Abstract : Intravitreal sulfur hexafluoride gas injection is a low cost and minimally invasive alternative for the treatment of vitreomacular traction syndrome.